2010
DOI: 10.1111/j.1574-6941.2010.00865.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nitrate on sulfur transformations in sulfidogenic sludge of a marine aquaculture biofilter

Abstract: The effect of NO(3)(-) addition on dissimilatory SO(4)(2-) reduction and sulfide conversion in organic-rich sludge from the digestion basin of a recirculating marine aquaculture system was studied. SO(4)(2-) reduction could only explain a minor fraction (up to 4-9%) of the observed total sulfide production (up to 35 mmol L(-1) day(-1)), indicating that the main source of sulfide in the sludge was not SO(4)(2-) reduction, but desulfuration during the decomposition of organic matter. Although NO(3)(-) inhibited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…It is also likely that some part of sulfides is generated in sulfidic waters via an alternative pathway, independent of SRB. Schwermer et al reported that desulfuration occurring during the decomposition of S-rich organic matter resulted in large H 2 S release in marine sludge, while microbial reduction of SO 4 2− accounted for only 4–9% of total H 2 S [ 68 ]. Besides, the authors indicated that nitrates in concentration exceeding 0.8 mM inhibited sulfate reduction (but not sulfuration) and induced sulfide oxidation (partially to S 0 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is also likely that some part of sulfides is generated in sulfidic waters via an alternative pathway, independent of SRB. Schwermer et al reported that desulfuration occurring during the decomposition of S-rich organic matter resulted in large H 2 S release in marine sludge, while microbial reduction of SO 4 2− accounted for only 4–9% of total H 2 S [ 68 ]. Besides, the authors indicated that nitrates in concentration exceeding 0.8 mM inhibited sulfate reduction (but not sulfuration) and induced sulfide oxidation (partially to S 0 ).…”
Section: Discussionmentioning
confidence: 99%
“…The biogeochemical importance of NO3- use by S-oxidizing bacteria has been widely recognized in marine sediments (Brettar and Rheinheimer, 1991) as well as freshwater sediments (Brunet and GarciaGil, 1996; Whitmire and Hamilton, 2005) and groundwater systems (Engesgaard and Kipp, 1992; Jorgensen et al, 2009). This process is used to mitigate toxic sulfide production in organic-rich sludge through NO3- - mediated sulfide oxidation (Schwermer et al, 2010). Vice versa , elemental sulfur has also been applied to wastewater treatment to remove NO3- by coupled sulfur oxidation and NO3- reduction (Sierra-Alvarez et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…High organic matter in the sediment can stimulate sulfate reduction via consumption of DO followed by a decrease in ORP in sediment or by providing increased quantities of electron donors for sulfate-reducing bacteria (Holmer & Storkholm 2001). Rates of sulfate reduction (R(T-H 2 S)) in this study (<0.26 μmol cm -3 h -1 ) were substantially higher than those of natural sediments in acidic lakes (Kühl et al 1998) and sandy intertidal sediments (de Beer et al 2005) (<0.01 μmol cm -3 h -1 ), while they were comparable to those of anaerobic sewer biofilm (Mohanakrishnan et al 2009) and organic-rich sludge in a marine aquaculture system (Schwermer et al 2010) (<1.0 μmol cm -3 h -1 ). Thus, these results indicate a massive input of organic matter to Tokyo Bay sediments is occurring.…”
Section: Discussionmentioning
confidence: 45%